The cost and feasibility of marine coastal restoration. Issue 4 (June 2016) - Bayraktarov, Elisa; Saunders, Megan I.; Abdullah, Sabah; Mills, Morena; Beher, Jutta; Possingham, Hugh P.; Mumby, Peter J.; Lovelock, Catherine E.
Abstract: Land‐use change in the coastal zone has led to worldwide degradation of marine coastal ecosystems and a loss of the goods and services they provide. Restoration is the process of assisting the recovery of an ecosystem that has been degraded, damaged, or destroyed and is critical for habitats where natural recovery is hindered. Uncertainties about restoration cost and feasibility can impede decisions on whether, what, how, where, and how much to restore. Here, we perform a synthesis of 235 studies with 954 observations from restoration or rehabilitation projects of coral reefs, seagrass, mangroves, saltmarshes, and oyster reefs worldwide, and evaluate cost, survival of restored organisms, project duration, area, and techniques applied. Findings showed that while the median and average reported costs for restoration of one hectare of marine coastal habitat were around US80 000 (2010) and US1 600 000 (2010), respectively, the real total costs (median) are likely to be two to four times higher. Coral reefs and seagrass were among the most expensive ecosystems to restore. Mangrove restoration projects were typically the largest and the least expensive per hectare. Most marine coastal restoration projects were conducted in Australia, Europe, and USA, while total restoration costs were significantly (up to 30 times) cheaper in countries with developing economies. Community‐ or volunteer‐based marine restoration projects usually have lower costs. Median survival of restored marine and coastal organisms, often assessed only within the first one to two years after restoration, was highest for saltmarshes (64.8%) and coral reefs (64.5%) and lowest for seagrass (38.0%). However, success rates reported in the scientific literature could be biased towards publishing successes rather than failures. The majority of restoration projects were short‐lived and seldom reported monitoring costs. Restoration success depended primarily on the ecosystem, site selection, and techniques applied rather than on money spent. We need enhanced investment in both improving restoration practices and large‐scale restoration.